Introduction to counseling. - A. Hamid, Siti Zubaidah (Universiti Sains Malaysia, 1980)
It is very difficult to secure any agreement on a definition of counseling (Patterson, 1969). Any given professional group of counselor usually represents at least several different orientations and preparations.